Pengaruh Penggunaan Media Pembelajaran Phet Terhadap Hasil Belajar Materi Pecahan Pada Siswa Kelas 2 SDN Socah - Marsha Amelia Putri; Naila Dwi Maulidia; Ika Dian Rahmawati (PADMA, 2026)
This research was conducted to evaluate how PhET media affects the performance of second-grade students learning fractions at SDN Socah 2 Bangkalan. A quantitative methodology was employed using a one-group pretest-posttest experimental design. The participants included 24 students selected through total sampling. Data collection techniques included observation, interviews, documentation, alongside pre-tests and post-tests. The data analysis was carried out by implementing the N-Gain test, the Kolmogorov-Smirnov test for assessing normality, and the Paired Sample T-Test, utilizing SPSS software. Findings indicated an increase in the average score from 64.58 in the pre-test to 78.75 in the post-test. The N-Gain score of 0.3563 was deemed moderate. Additionally, results from the Paired Sample T-Test showed a significance level of 0.000.